Umbrüche, Kontinuitäten und Strukturwandel am Finanzplatz Köln nach dem Zweiten Weltkrieg - Harald Wixforth (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– Cologne has also benefited as a financial center from the specific momentum of the "economic miracle" since the 1950s. On the one hand, previously existing structures such as the excellent position of private bankers could be built on in Cologne, on the other hand, new business fields such as retail customers gained significance. In addition, new actors such as the Bank für Gemein-wirtschaft (Bank for Social Economy) established them-selves, as did special institutions for leasing and other financial services. Whether the private banks in Cologne were among the winners of the structural change that continued until the crisis in the mid-1970s, or rather the savings banks or credit unions instead, would have to be investigated empirically through comprehensive profita-bility analyses of individual banks. If one considers the end of renowned private banking houses, or even larger institutions such as Dresdner Bank it appears, currently anyway, that the local savings banks benefited most from the structural changes. Assessing whether such an opinion holds true already for the mid-1970s, as the savings bank organization was confronted with considerable problems, requires additional research.
Keywords: G21; G22; N24; N94; 330